A dual‐band amplifier with flexible frequency ratios. Issue 10 (October 2015) - Chen, Te‐Chuan; Hua, Wei; Gbele, Kokou; Zhang, Hualiang; Xin, Hao
ABSTRACT This article presents a dual‐band amplifier with flexible frequency ratios. The amplifier features novel Wilkinson power divider/combiner with dual‐band property that allows large frequency ratio (2.16–4.9) between its first and second operating bands. The measured combining efficiency on a stand‐alone combiner is 97% at 2.25 GHz and 75% at 5.25 GHz. A 2.25/5.5 GHz prototype amplifier is tested to verify dual‐band functionality. Measured linear gains are 12.85 dB and 12.07 dB at the first and second frequency bands, respectively. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:2242–2247, 2015